Psychological assessment tools utilized in sports injury treatment outcomes research: A review - Everhart, J. S.; Harris, K.; Chafitz, A.; Kirven, J. C.; Abouljoud, M.; Schiele, S.; Emery, C.; Flanigan, D. C. (Journal of Sports Science & Medicine, 2020)
The use of self-report psychological assessment tools in outcomes research has become increasingly frequent, though many sports medicine providers and researchers are unfamiliar with these instruments. We conducted a systematic search of the sports medicine literature in PubMed, Scopus, SPORTDiscus, and Google Scholar of studies published on or before November 1st, 2019. Included psychological self-assessment tools were limited to those in a written self-assessment format and were used in musculoskeletal sports injury or concussion treatment outcome studies. Both pre- or post-treatment psychological assessments were included. Thirty-four assessment scales of psychological factors were utilized across 152 sports injury treatment outcomes studies. Six assessment tools were utilized in 5 or more studies and the remaining 28 were utilized in 4 or fewer studies. Many of the utilized scales have adequate assessment and reporting of internal consistency reliability, supporting further reliability and validation studies for use in sports injury treatment outcomes research.